1969
DOI: 10.1002/zaac.19693690314
|View full text |Cite
|
Sign up to set email alerts
|

IR‐ und 1H‐NMR‐spektroskopische Untersuchungen von Metallalkylverbindungen

Abstract: Es wurden die IR‐Spektren von LiCH3, Be(CH3)2, Li2CH2 und MgCH2 aufgenommen und zugeordnet. Weiterhin werden die Protonen‐Resonanz‐Spektren von LiCH3, Be(CH3)2 und Mg(CH3)2 mitgeteilt. Aus beiden Spektren wird abgeleitet, daß mit abnehmender Elektronegativität des Elementes die Bindung zur Methylgruppe immer polarer wird. Damit bekommt die CH‐Bindung zunehmenden p‐Charakter. Dies trifft weitgehend für die beiden Methylenverbindungen zu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1971
1971
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…4 The symmetry point group of the averaged ion is -J. A basis set of triple-{ quality for the valence shell was selected for oxygen by adding one s function (exp 0.09) and one p function (exp 0.07) to the (9,5) set of Huzinaga.8 The basis set for oxygen is therefore (10,6) contracted into [4,3]. Chem.…”
Section: Computational Detailsmentioning
confidence: 99%
“…4 The symmetry point group of the averaged ion is -J. A basis set of triple-{ quality for the valence shell was selected for oxygen by adding one s function (exp 0.09) and one p function (exp 0.07) to the (9,5) set of Huzinaga.8 The basis set for oxygen is therefore (10,6) contracted into [4,3]. Chem.…”
Section: Computational Detailsmentioning
confidence: 99%
“…IR-spectroscopic investigations of [MgCH 2 ] n werep erformed and furthers tudies revealed that the transfer of methylene groups from [MgCH 2 ] n to Cp 2 ZrMeCl affords the zirconium sandwichc omplexes[ Cp 2 Zr(X)(m-CH 2 )] 2 (X = Me, Cl) and [Cp 2 Zr(m-CH 2 ) 2 ] 2 . [81,86] [MgCH 2 ] n was also the subject of am atrix IR-spectroscopic study. [87] Noteworthy,t heoretical (DFT) calculations have been performed not only on the Mg II methylidene but also on the calcium analog [CaCH 2 ] n and other metal methylidenes.…”
Section: Reinera Nwander Studied Chemistry At Thementioning
confidence: 99%
“…IR‐spectroscopic investigations of [MgCH 2 ] n were performed and further studies revealed that the transfer of methylene groups from [MgCH 2 ] n to Cp 2 ZrMeCl affords the zirconium sandwich complexes [Cp 2 Zr(X)(μ‐CH 2 )] 2 (X=Me, Cl) and [Cp 2 Zr(μ‐CH 2 ) 2 ] 2 . [MgCH 2 ] n was also the subject of a matrix IR‐spectroscopic study .…”
Section: Alkylidenesmentioning
confidence: 99%
“…Das IR-Spektrum von festem (CH3Li), wurde mehrfach [35][36][37][38] in verschiedenen Einbettungen untersucht; auch das Spektrum von monomerem CH3Li in festem Argon39) ist bekannt. Die Bandenzuordnung kann nunmehr als gesichert gelten; manche friiheren Irrtumer beruhen auf Verunreinigungen oder Zersetzungsprodukten der sehr reaktionsfahigen Substanz.…”
Section: Ir-spektren Von (Ch3na)4 Und Anderen Methylverbindungenunclassified